Systematic review of the safety, immunogenicity, and effectiveness of COVID‐19 vaccines in pregnant and lactating individuals and their infants. Issue 3 (13th November 2021) - Fu, Winnie; Sivajohan, Brintha; McClymont, Elisabeth; Albert, Arianne; Elwood, Chelsea; Ogilvie, Gina; Money, Deborah
Abstract: Background: There is significant risk of complications and vulnerability to severe COVID‐19 disease in pregnancy, yet hesitancy exists around COVID‐19 vaccination during pregnancy and lactation. Objective: To summarize the safety, immunogenicity, and effectiveness of COVID‐19 vaccines in pregnancy and lactation. Search strategy: A systematic search of MEDLINE, Embase, PubMed, medRxiv, and bioRxiv. Selection criteria: Identified original studies published on pregnant and/or lactating individuals who received one or more doses of a COVID‐19 vaccine. Data collection and analysis: A descriptive summary organized by safety, immunogenicity, and effectiveness outcomes of COVID‐19 vaccination in pregnancy and lactation. Main results: In total, 23 studies were identified. Humoral response and functional immunity were interrogated and found. Increasing placental transfer ratios in cord blood were associated with increasing time from the first vaccine dose to delivery. Safety data indicated that pregnant and lactating populations experienced vaccine‐related reactions at similar rates to the general population. No increased risk of adverse obstetrical or neonatal outcomes were reported. One study demonstrated that pregnant individuals were less likely to experience COVID‐19 when vaccinated. Conclusion: COVID‐19 vaccination in pregnant and lactating individuals is immunogenic, does not cause significant vaccine‐related adverse events or obstetrical and neonatal outcomes, and is effective in preventing COVID‐19 disease. Abstract : The present systematic review found that COVID‐19 vaccines are safe, immunogenic, and effective during pregnancy and lactation.